From Gaps to Solutions: Semi-Structured Interviews to Identify Care Gaps in Breast Cancer Care and How to Solve Them with Digital Solutions - Pross, Therese; Karsten, Maria Margarete; Blohmer, Jens-Uwe (Geburtshilfe und Frauenheilkunde, 2024)
Standardized treatment pathways should make it easier for medical staff and patients to achieve the best possible individual treatment outcome by making sure all relevant information are taken into consideration. The aim of this paper is to identify gaps in care along the treatment pathway through semi-structured patient interviews. Subsequently, it will be discussed if mobile health applications can close these identified gaps in care.Nine semi-structured interviews of patients with invasive lobular breast cancer were conducted in March 2023 in German at the breast cancer center at Charité Universitätsmedizin Berlin, which were subsequently transcribed word for word and processed using a thematic analysis approach.Eight recurring themes are identified in the patient interviews: 1. Limited capacity to absorb information, 2. Discrepancy between information needs and information provision, 3. Need for individual initiative, 4. Uncertainty, 5. not being seen and heard, 6. Patient’s desires and suggestions for improvement, 7. Use of mobile health apps, 8. Support through an app for patients.The identified gaps in care of breast cancer patients can be largely addressed through the use of digital health solutions after the establishment of regulatory frameworks, thus improving care for patients with early breast cancer.The interviews were done within a registry for which ethical approval was obtained by the Ethics Committee of Charité Universitätsmedizin Berlin EA4/180/17.
Keywords: breast cancer; treatment pathway; patient pathway; patient journey; care gap; mHealth; eHealth; digital health; oncology